The Existence of Work Agreements for a Specific Time Before and After the Job Creation Law Number 11 of 2020 - Rini, Astiti Swanita (Universitas Syiah Kuala, 2023)
The purpose of this research is to analyze the criteria for the period of time and types of work that are used as the basis for employment relations in work agreements for a certain time when viewed from the Law Employment and analyzing the protection of continuity of work for workers/labourers with a Fixed Time Work Agreement. The type of research that the author uses is normative legal research, namely legal research that places law as a building system of norms. The intended system of norms is regarding principles, norms, rules of laws and regulations, court decisions, agreements and doctrines (teachings). The research results obtained are first, work agreements often do not go well and according to initial expectations. There are times when there are disputes or differences of opinion from each party. Therefore there must be a work agreement made in writing. Second, the existence of a work agreement makes the work relationship bound and cannot be separated from the agreement. Regulations related to the employment relationship system with a Specific Time Work Agreement (PKWT) are a form of accountability that must be complied with by companies/employers. However, PKWT still has a negative impact on workers/labourers even though there are laws that regulate it. Employers/companies commit many violations related to the types of work that can be carried out with the Specific Time Work Agreement (PKWT) system as well as violations related to the specified time period of the Work Agreement (PKWT).